Observation of coherent delocalized phonon-like modes in DNA under physiological conditions - González-Jiménez, Mario; Ramakrishnan, Gopakumar; Harwood, Thomas; Lapthorn, Adrian J.; Kelly, Sharon M.; Ellis, Elizabeth M.; Wynne, Klaas (Nature communications, 2016)
Underdamped terahertz-frequency delocalized phonon-like modes have long been suggested to play a role in the biological function of DNA. Such phonon modes involve the collective motion of many atoms and are prerequisite to understanding the molecular nature of macroscopic conformational changes and related biochemical phenomena. Initial predictions were based on simple theoretical models of DNA. However, such models do not take into account strong interactions with the surrounding water, which is likely to cause phonon modes to be heavily damped and localized. Here we apply state-of-the-art femtosecond optical Kerr effect spectroscopy, which is currently the only technique capable of taking low-frequency (GHz to THz) vibrational spectra in solution. We are able to demonstrate that phonon modes involving the hydrogen bond network between the strands exist in DNA at physiologically relevant conditions. In addition, the dynamics of the solvating water molecules is slowed down by about a factor of 20 compared with the bulk. Terahertz-frequency vibrational modes are thought to play a key role for DNA biological functions, yet observation of these fluctuations in solution has proven difficult so far. Here, the authors use femtosecond optical Kerr-effect spectroscopy to demonstrate their existence in physiologically relevant conditions.